The limitations and diameter dependence of carrier drift velocity in carbon nanotubes - Ahmadi, Mohammad Taghi; Ismail, Razali; Arora, Vijay Kumar (ACECR, 2009)

(untitled)
Due to the chemical stability and perfection of Carbon Nanotubes (CNTs) structure, carrier mobility is not affected by processing and roughness scattering as it is in the conventional semiconductor channel. Therefore, CNTs are being considered as viable candidates for high-speed applications. The mobility and saturation velocity are the two important parameters that control the charge transport in a conducting MOSFET channel. It is shown that the high mobility does not always lead to higher carrier velocity. Owing to the high electric-field streaming, the ultimate drift velocity in semiconducting CNTs are based on the asymmetrical distribution function that converts randomness in zero-field to streamlined one in a very high electric field. The limitation drift velocity is found to be appropriate thermal velocity for non- degenerate regime, increasing with the temperature, but independent of carrier concentration. In this condition, velocity rises with increasing the diameter. However, the limitation drift velocity is the Fermi velocity for degenerate regime which increasing with carrier concentration but independent of the temperature. Moreover, in degenerate regime, degeneracy occurs at lower values of the carrier concentration with increasing the CNTs diameter